Shrinkwrap geometry defeaturing for finite element analysis for a wheel and hub model. Issue 3 (3rd May 2016) - Pike, Matthew G.; Feng, David X.; Myers, Michael R.
ABSTRACT: This manuscript presents an automated approach to accurately estimate structural performance for component assemblies using a shrinkwrap geometry defeaturing process for a wheel and hub model. Defeaturing is a popular geometry simplification technique that suppresses features within the geometry to decrease computational resources and time. Shrinkwrap defeaturing is an automated modeling technique that represents the exterior shape of the original full-featured geometry with a collection of surfaces for an abstract representation. The shrinkwrap defeaturing can be used on full-featured computer aided design components that are parts of an assembly but are not undergoing structural analysis and are included to transmit loads within the assembly. Of interest is the automated finite element structural analysis of the assembly. The proposed shrinkwrap approach is reviewed and assessed with a full-featured geometry model as well as other geometry defeaturing methods. A numerical example of a wheel and hub is presented to show that the proposed shrinkwrap approach displays better estimated structural performance than use of spider modeling, which incorporates 1D-3D model connections. GRAPHICAL ABSTRACT: